Pre-transplant dialysis vintage and post-transplant outcomes: A retrospective cohort study in Korean kidney transplant recipients - Eunju Jang; Ki Yoon Moon; Sang Seob Yun; Sun Cheol Park (PLoS ONE, 2026)
Background Kidney transplantation (KT) is the preferred treatment for end-stage renal disease (ESRD) due to its advantages over dialysis. Although the benefits of preemptive KT are well established, the association between pre-transplant dialysis duration and post-transplant outcomes remains uncertain. Objective To evaluate the association between pre-transplant dialysis vintage and post-transplant outcomes in Korean KT recipients using real-world data from a tertiary transplant center. Methods We retrospectively evaluated 1,843 first KT recipients transplanted between 2006–2021. Dialysis duration was used as a categorical variable divided by tertiles according to distribution of time of analysis, and preemptive transplantation was categorized as a separate group. Primary outcomes included death-censored graft loss, all-cause mortality and composite outcomes. Survival was assessed using Kaplan–Meier and Cox proportional hazards models at a 95% confidence level. A deceased-donor KT (DDKT) subgroup analysis was also performed. Results 369 patients underwent preemptive KT, and 1,474 dialysis-exposed recipients were categorized into tertile 1 (n = 492), tertile 2 (n = 491), and tertile 3 (n = 491), with mean pre-transplant dialysis durations of 1.2, 21.4, and 107.6 months, respectively. Compared with preemptive KT, all-cause mortality did not differ in the first or second tertiles but was significantly higher in the third tertile (aHR 3.55; 95% CI 1.43–8.81; p = 0.006). In the overall cohort, the third tertile was also associated with higher risks of death-censored graft failure and the composite outcome. However, in the deceased-donor KT subgroup, death-censored graft failure did not differ significantly across tertiles, and the composite outcome did not show a monotonic dose-response pattern. Conclusions Prolonged pre-transplant dialysis was associated with a higher risk of all-cause mortality, whereas its association with graft failure was less consistent, particularly among deceased-donor KT recipients.